Unwillingly informed: The prosocial impact of third-party informers - Zachary Grossman; Tony Hua; Jo Thori Lind; Karine Nyborg (University of Oslo, Department of Economics, 2025)
While people often avoid learning about negative social consequences of their actions in order to behave selfishly, many social situations involve another person who is in a position to impose this information. How does the presence of a potential informer affect information, behavior, and welfare in social decisions with moral wiggle-room? We introduce a third-party informer into the moral wiggle-room game. Almost half of the dictators tried to avoid information only to have it imposed upon them by the informer. These unwillingly-informed dictators frequently revised their behavior to benefit the recipient, even at their own expense. Given an opportunity to reward informers, most dictators chose to do so, but those who had bad news thrust upon them by the informer were more likely to withhold the reward. Interestingly, a subtle change in the choice interface - separating the dictator's ignorance and allocation choices in two separate screens-caused a substantial reduction in the share of dictators choosing ignorance.
Keywords: D83; C72; C91; 330; willful ignorance; information avoidance; unethical behavior; online experiment